PENERAPAN PEMAHAMAN MENGENAI HAKIKAT MANUSIA DALAM PROSES PENDIDIKAN TERHADAP SISWA MENENGAH ATAS - Roprop Latiefatul Millah (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2020)
Human nature is the core found in humans. In the perspective of Islamic Education Philosophy is something very important and fundamental that can determine human life. The target of education is humans who intend to help students to grow and develop their human potential. Human potential is an ability that might be developed to become a human. Education should be able to humanize humans. By basing on an understanding of human nature, educational activities and processes are carried out and aim to develop a more normative human personality. Because, without a true understanding of what, who, why, and for what humans, education will fail to realize the ideals of human beings. The ultimate goal of education is to make the person based on the principle of real realization, namely to realize the potential that already exists in humans in the form of moral potential, skills and physical development.